The Status of Oxidants and Antioxidants in Children with Nephrotic Syndrome - Hertanti Indah Lestari; Eka Febri Zulissetiana; Ardesy Melizah (Bioscientia Medicina : Journal of Biomedicine and Translational Research, 2018)
Background: The nephrotic syndrome (NS) resistance and relapse to treatment pose challenges in the management of NS. Several experimental studies on both animals and humans have assessed the association between NS and the balance between the oxidants and anti-oxidants. The study aims to compare the status of oxidants and anti-oxidants of NS patients between the massive proteinuria, the remission, the steroid resistance and the control groups. Methods: a cross-sectional design to assess the status of oxidants and antioxidants in children with the nephrotic syndrome. The eligible subjects were divided into four groups, the massive proteinuria group, the remission group, the steroid resistant group and the control group. The status of oxidants and anti-oxidant were evaluated with the Malondialdehyde (MDA) and the Total Antioxidant Status (TAS), respectively. Results: The highest mean MDA levels was observed in the steroid resistant group followed by the massive proteinuria group and the remission group. The mean MDA level of the proteinuria group (massive proteinuria and steroid-resistant) is higher than the remission group. The mean TAS levels in the remission group were higher than the massive proteinuria group, but the difference was not statistically significant. Moreover, the mean difference of SAT between the proteinuria group and without proteinuria was not statistically significant. Conclusions: The oxidative stress marker (MDA) was higher in the NS patients with proteinuria than the patients without proteinuria. The difference in the total anti-oxidant status in NS patients with massive proteinuria, remission and steroid resistance were not statistically significant. Keywords: Nephrotic syndrome, oxidative stress, anti oxidant